MicroRNA-200 as potential diagnostic markers for colorectal cancer: meta-analysis and experimental validation - Peng, Zongyu; Zhu, Wenru; Dai, Jinzhao; Ju, Fang (Cellular and Molecular Biology, 2018)
Members of microRNA(miR)-200 family is proposed as promising biomarkers for colorectal cancer (CRC). However, their expression in CRC patients, and whether them could identify as new biomarkers of cancers are inconsistent and controversy. Therefore, a meta-analysis was performed to assess the diagnostic value of miR-200 family members in CRC patients. This meta-analysis screened 6 studies, including 191 patients with colorectal cancer at stage IV, 446 patients with colorectal cancer at stage I~III and 98 normal controls, and performed using bivariate and hierarchical summary receiver operating characteristic (HSROC) models. The quality of the eligible studies was assessed according to Quality Assessment of Diagnosis Accuracy Studies-2. The pooled sensitivity and specificity of miR"‘141 alone for CRC diagnosis were 82% and 75%, respectively. The diagnostic odds ratio (DOR) value was 13.21 [95% confidence interval (CI), 7.00"‘24.95], and the area under the curve (AUC) was 0.85 (95% CI, 0.82"‘0.88). The pooled sensitivity and specificity of total miR-200 family members were 79% and 71%, respectively. In the HSROC model, the estimate for the "Lambda" was 2.48 (95% CI,1.50-3.46). Finally, we detected the miR-141 in 20 CRC patients and 20 healthy. Results showed that serum miR-141 was overexpressed in CRC patients. Overall, miR-141 in miR-200 family has a good sensitivity and moderate specificity for CRC diagnosis.